TEACHING MATERIALS FOR BAHASA INDONESIA READING SKILLS BASED ON LOCAL WISDOM WITH A QUANTUM APPROACH: Research & Development on Teaching Materials for Grade IV Elementary Schools - Saota, Erlina; Rasyid, Yumna; Pujiati, Hanip (English Education Department, 2023)
This study aimed at developing teaching materials for Bahasa Indonesia reading skills for Grade IV Elementary School students based on local wisdom using a Quantum approach in South Nias District. By applying Borg and Gall's R&D design, this study involved 92 random samples of students. Data was collected through questionnaires and tests. The results of the study using the t-test obtained tcount of 23.40 higher than ttable of 2.63. In other words, there was a significant difference after using the developed teaching material product. It can be concluded that the developed teaching materials for Bahasa Indonesia reading skills based on local wisdom with a Quantum approach was very effective for teaching reading in grade IV, Public Elementary School, South Nias District. The implications of this study regarding reading achievement, local wisdom, and teacher's strategies are also discussed.